Making All Voices Count: A Slam Dunk? - Integrity, Global (2012)
Yesterday, I had the chance to attend the public launch of a new gover nment transparency and accountability funding mechanism – Making All V oices Count. Held at USAID headquarters, the discussion featured a ver itable who’s who of open government and transparency practitioners in the Washington area; probably 250 people were packed into the room. (A nnouncing a …